2017
DOI: 10.1093/ajcp/aqx037
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of Serum Free Light Chain Analysis

Abstract: FLC analysis requires continuous awareness of analytical limitations. Monitoring of disease response requires FLC analysis on the same platform using the same reagents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…The technical and analytical characteristics of the N-Latex FLC and Freelite assays have been thoughtfully described elsewhere ( 7 - 10 ). Previous evidence has shown that numerical values produced by the two different systems can have remarkable differences and this aspect has also been evidenced in our study, where higher concentrations are paralleled by an increase in absolute differences ( 11 , 12 ). Several causes can be preferred for explaining inter-assay variability.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The technical and analytical characteristics of the N-Latex FLC and Freelite assays have been thoughtfully described elsewhere ( 7 - 10 ). Previous evidence has shown that numerical values produced by the two different systems can have remarkable differences and this aspect has also been evidenced in our study, where higher concentrations are paralleled by an increase in absolute differences ( 11 , 12 ). Several causes can be preferred for explaining inter-assay variability.…”
Section: Discussionsupporting
confidence: 87%
“…First, the Freelite method uses polyclonal Ab, whilst the N-Latex is based on a cocktail of monoclonal Ab. It is hence conceivable that less antigenic determinants may be better recognized by the N-Latex assay, whereas some FLC abnormally expressed in plasma cell dyscrasia could escape detection ( 2 , 11 , 12 ). Previous data underpins that the discrepancies observed between the two methods may be attributable to polymerization of FLC, leading to potential overestimation using the Freelite method, with concurrent underestimation using the N-Latex assay due to binding sites masking ( 13 , 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…Messiaen AS et al . documented a lower correlation coefficient for FLC lambda (0.93) than FLC kappa (0.98) results in comparison of monoclonal and polyclonal reagent on the same analyser ( 19 ). Our results demonstrate that occasionally progressive disease would not be recognized in certain patients using one of the applied analysers.…”
Section: Discussionmentioning
confidence: 97%
“…Numerous studies present evaluation results of FLCs test. Most of them involve evaluation of polyclonal reagent on different not reagent-optimized analytical platforms for FLCs tests ( 19 , 22 ). This evaluation study is conducted on reagent-optimized analysers.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the tests measure the presence of the soluble immune complexes by detecting the changes in turbidity through nephelometric or turbidimetric methods. These methods can suffer from high imprecision at low concentrations, nonlinear immunoreactivity on dilutions, and/or the inability to detect antigen excess, leading to underestimation of mFLC concentration [14–17], all of which can potentially impact the κ/λ ratio. Freelite from The Binding Site was the first available method in 2001 and has been developed as six independent tests adapted to different nephelometry and turbidimetry analyzers.…”
Section: Introductionmentioning
confidence: 99%